2019
DOI: 10.14421/jpi.2018.72.267-280
|View full text |Cite
|
Sign up to set email alerts
|

Headmaster’s Leadership in Solving Problems at Islamic Elementary School (SDI) Hikmatul Fadhillah Medan

Abstract: The school headmaster is at the forefront in cooperating to build human relation at school as well as its surrounding environment. Harmonious relation should be planned and implemented by the school headmaster as the top leader. The school headmaster is a leader, and a teacher is a colleague and a friend at work. In school management, headmaster-teacher relation is a mutual relation in making efforts to achieve a better quality of school management. This article uses naturalistic phenomenological approach by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Leaders can diagnose problems encountered in implementing a program through their working relationships with teachers. Leaders can also make policies or decisions regarding solutions that can be done to overcome these problems (Rahmi, 2019). It can even be said that leaders in educational institutions are the main instruments in carrying out program evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Leaders can diagnose problems encountered in implementing a program through their working relationships with teachers. Leaders can also make policies or decisions regarding solutions that can be done to overcome these problems (Rahmi, 2019). It can even be said that leaders in educational institutions are the main instruments in carrying out program evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Kepala sekolah adalah sesorang yang diangkat karena kemampuannya dalam memimpin suatu lembaga sekolah (Rahmi, 2019). Dalam pendapat lain arti dari kepala sekolah adalah seorang tenaga fungsional guru yang diberi tugas untuk memimpin suatu sekolah, yang diselenggrakan proses belajar mengajar, atau interaksi antara guru dan siswa (Wahjosumidja dalam Ahmad Susanto, 2016).…”
Section: Pendahuluanunclassified
“…Sebagai mana kata (Barth, 2001), "The fact of the matter is that all teachers harbor leadership capabilities waiting to be unlocked and en-gaged for the good of the school ". Selain tugas dan tanggungjawab yang dibawa, kepala sekolah juga harus lebih cekatan atau reaktif terhadap perubahan zaman (Rahmi, 2019) Dalam Nanus (2001:95), Komariah (2003:93), Sujatno (2008:62) mengilustrasikan bahwa ada 4 (empat) peran penting bagi kepemimpinan efektif salah satunya adalah agen perubahan, bahwa pemimpin harus mampu memprediksikan berbagai perubahan dan perkembangan lingkungan global dan membuat antisipasi tentang implikasinya terhadap lembaga atau instansi yang dipimpinnya, mampu membuat ketentuan khusus bagi perubahan yang diisyaratkan visinya, serta mampu mempromosikan temuannya dengan partisipasi orang-orang untuk menghasilkan kemajuan yang diinginkan.…”
Section: Pendahuluanunclassified
“…Meanwhile, the ways to deal with conflicts include: introduction, diagnosis, agreeing on a solution, implementation, and evaluation. Rahmi (2018) showed that principals tend to overcome problems or conflicts with Human Relations that are performed by paying attention to religious values, personality, friendship, and polite conversation.…”
Section: The Uniqueness Of Problem Solvingmentioning
confidence: 99%